1978
DOI: 10.1177/028418517801900209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Somatostatin on Intestinal Motility

Abstract: The effect of somatostatin on intestinal motility has been investigated. The demonstrated inhibition of the motility has proved to be suitable for performing double contrast examinations of the small intestine, particularly as the tolerability to somatostatin is better than to other comparative substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…Nonetheless, there is strong indirect evidence that the principal mechanism for the increased percentage of deoxycholic acid in the bile of patients with octreotide‐associated gall‐bladder stones is prolongation of intestinal transit. Thus, several previous studies have reported that both native somatostatin 60–63 and its analogue octreotide 35 , 64–68 prolong mouth‐to‐caecum transit times. In paired, before and during treatment, studies of acromegalic patients, we also showed 67 that the mean colonic transit time increased by approximately 15 h, with an associated linear increase in serum deoxycholic acid (expressed as a percentage of serum total bile acids).…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, there is strong indirect evidence that the principal mechanism for the increased percentage of deoxycholic acid in the bile of patients with octreotide‐associated gall‐bladder stones is prolongation of intestinal transit. Thus, several previous studies have reported that both native somatostatin 60–63 and its analogue octreotide 35 , 64–68 prolong mouth‐to‐caecum transit times. In paired, before and during treatment, studies of acromegalic patients, we also showed 67 that the mean colonic transit time increased by approximately 15 h, with an associated linear increase in serum deoxycholic acid (expressed as a percentage of serum total bile acids).…”
Section: Discussionmentioning
confidence: 98%
“…Also, because our patients have had diabetes for a mean of 16 yr, they may be more prone to develop subclinical autonomic visceral neuropathy. The latter could be aggravated by the known inhibitory effects of the analogue on Gl motility and nutrient absorption (46,47). Paradoxically, SMS 201-995 has been shown to be effective for intractable and life-threatening chronic diarrhea in a diabetic patient (48) and patients with watery-diarrhea-hypokalemic-achlorhydric syndrome due to vasoactive intestinal polypeptide-secreting tumor (49,50) and ileostomy (51).…”
Section: Discussionmentioning
confidence: 99%
“…SP, which is known to increase intestinal transit (Liljedahl et al, 1958), was lower in the plasma of PCSK2-KO mice (Fig. 3A); whereas GLP-1, GLP-2 and SS, which are known to slow this transit (Bozkurt et al, 2002;Efendic and Mattsson, 1978), were higher (Fig. 3, panels B, C and D).…”
Section: Plasma Levels Of Neuroendocrine Peptidesmentioning
confidence: 96%
“…These include, among numerous others, the precursors of cholecystokinin (CCK), glucagon-like peptide-1 (GLP-1) and GLP-2, neuropeptide Y (NPY), peptide YY (PYY), somatostatin (SS) and substance P (SP). SP stimulates GI motility (Niel, 1991), whereas CCK, GLP-1, GLP-2 and SS inhibit it (Anvari et al, 1998;Bozkurt et al, 2002;Efendic and Mattsson, 1978;Grider, 1994;von der Ohe et al, 1992). NPY stimulates appetite (Lynch et al, 1994), whereas PYY and GLP-1 reduce it (McMahon and Wellman, 1998;Ueno et al, 2008).…”
Section: Introductionmentioning
confidence: 99%